Use of sodium polyphosphates with different linear lengths in the production of spreadable processed cheese - Nagyová, G; Buňka, F; Salek, R N; Černíková, M; Mančík, P; Grůber, T; Kuchař, D (Journal of dairy science, 2014)
The objective of this study was to describe the dependence of textural properties (hardness, cohesiveness, and relative adhesiveness) of processed cheese spreads on the proportion of disodium phosphate (DSP), tetrasodium diphosphate (TSPP), and sodium salts of polyphosphate in ternary mixtures of emulsifying salts. Sodium salts of polyphosphate with different mean lengths (n ≈ 5, 9, 13, 20, and 28) were used. Pentasodium triphosphate (PSTP) was used instead of TSPP in the second part of the study. Products with and without pH adjustment were tested (the target pH value was 5.60-5.80). Textural properties of the processed cheese were observed after 2, 9, and 30 d of storage at 6°C. Hardness of the processed cheese with a low content of polyphosphate increased at a specific DSP:TSPP ratio (~1:1 to 3:4). This trend was the same for all the polyphosphates used; only the absolute values of texture parameters were different. The same trends were observed in the ternary mixtures with PSTP, showing lower final values of hardness compared with samples containing TSPP. Hardness and cohesiveness decreased and relative adhesiveness increased in the samples with increased pH values and vice versa; the main trend remained unchanged.
Keywords: Food Handling; Emulsions; polyphosphate; Cheese; Salts; soli; difosfáty; tvrdost; processed cheese; skladování potravin; Hydrogen-Ion Concentration; Food Storage; emulze; koncentrace vodíkových iontů; sýr; Hardness; emulsifying salt; Animals; polyfosfáty; Phosphates; Polyphosphates; zvířata; fosfáty; textural property; Diphosphates; manipulace s potravinami